Results of allogeneic hematopoietic stem cell transplantation for chronic myelogenous leukemia patients who failed tyrosine kinase inhibitors after developing BCR-ABL1 kinase domain mutations - Jabbour, Elias (American Society of Hematology, 2011)
Hematopoietic stem cell transplantation (HSCT) is effective therapy for patients with chronic myelogenous leukemia (CML) but is now mostly indicated for patients who develop resistance to tyrosine kinase inhibitors (TKIs), which can be associated with point mutations in BCR-ABL1. We reviewed the outcomes of imatinib-resistant CML patients (chronic phase, n = 34; accelerated phase [AP], n = 9; and blast phase [BP], n = 4) who underwent HSCT and had BCR-ABL1 sequencing. Mutations were found in 19 patients (40%); 15 of 19 had advanced CML (AP + BP + second chronic phase). Patients with mutations were more likely to transform to AP/BP at time of imatinib failure (69% vs 35%, P = .03). Forty-two patients (89%) responded to HSCT: 32 (68%) had at least a major molecular response. The 2-year event-free survival was 36% and 58% (P = .05) for the mutant and nonmutant groups, respectively; and the 2-year overall survival was 44% and 76% (P = .02), respectively. HSCT is an important salvage option for TKI-resistant patients with or without BCR-ABL1 mutations. Patients with mutations were more likely to develop advanced disease and had worse outcomes after HSCT. HSCT should be considered early for patients deemed to have a low probability of responding to second-generation TKI.